100% Watermelon Juice as a Food-First Intervention to Improve Cognitive Function: Ancillary Findings from a Randomized Controlled Trial. Issue 4 (2nd October 2021) - Crowe-White, Kristi M.; Nagabooshanam, Vinoth Aryan; Dudenbostel, Tanja; Locher, Julie L.; Chavers, Tinsley P.; Ellis, Amy C.
Abstract: Lycopene exhibits neuroprotective properties due to its antioxidant and anti-inflammatory functionality. As watermelon is a rich source of lycopene, pasteurized watermelon juice provides lycopene in its most bioavailable form. This study examined relationships between circulating lycopene, cognitive performance, and biomarkers of oxidative stress and inflammation in response to pasteurized 100% watermelon juice supplementation. A placebo-controlled, randomized, double-blind, crossover trial was conducted with postmenopausal women ( n  = 16, 60 + 4.1 years). Participants consumed two 360 mL servings of pasteurized 100% watermelon juice or a placebo beverage for 4 weeks. Fasting blood samples were collected, and cognitive tests were administered to assess various neurocognitive domains. Statistical analyses included mixed models and Spearman correlations. Serum lycopene exhibited a significant treatment effect ( p  = 0.002) with a mean increase of 81%. However, this increase was not associated with changes in oxidative stress, inflammation, or cognitive function. Additional research is warranted to determine dose-durational effects for promoting cognition.